RECENT DEVELOPMENT IN INVESTIGATION OF CHICKEN LEPTIN GENE: A REVIEW - Mahardhika, I Wayan Swarautama; Daryono, Budi Setiadi (Buletin Veteriner Udayana, 2021)
The leptin coding gene (LEP) investigation in several avian species has been carried out in-depth for over 20 years. Genomic expression of LEP gene in numbers of avian species has been identified, including Falco peregrinus and Falco cherrug , Pseudopodoces humilis , Taeniopygia guttata , Columba livia , Haliaeetus leucocephalus , Picoides pubescens, and Melopsittacus undulatus . However, molecular genetics identification of LEP gene expression in chicken ( G. g. gallus ) is still debated. The Indonesian indigenous chicken poultry industry is growing rapidly, with some limitations, one of which involves Indonesian indigenous chicken's productivity. Indonesian indigenous chicken contributes 23% of national food consumption annually. Increased productivity of Indonesian indigenous chicken can be achieved through selective breeding. Selective breeding seeks to improve the genetic quality of Indonesian indigenous chicken by empowering Indonesian indigenous chicken germplasm. Selective breeding allows the production of meat-type and layer-type hybrids with superior characteristics following the design of the specified crossing pattern. Selective breeding requires both Mendelian and molecular genetics as guidance and evaluation methods to maintain breeding direction effectiveness. Several identified genes that have a significant implication on chicken productivity have been researched thoroughly. However, several other important gene candidates, including the LEP gene, still require in-depth research. This review integrates several studies on the chicken LEP gene from the initial discovery until the latest breakthrough.